Understanding dietary behavior amongst those with diabetes and high blood glucose level in Kathmandu. - Caperon, Lizzie. (Tufts University. Tisch Library., 2019)
This poster assess the dietary behaviour changes amongst diabetes and high bold glucose levels in Kathmandu.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy